2006
DOI: 10.1007/s00240-006-0072-2
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive treatment of ureteral calculi in children

Abstract: A retrospective analysis was done to determine the efficacy of shock wave lithotripsy (SWL) and ureteroscopy in the treatment of paediatric ureteral calculi. We reviewed the records of 67 (35 boys, 32 girls) children (71 ureters) admitted to our clinic for treatment of ureteral calculi during 1990-2005. The initial treatment method was SWL in 80.3% (57 ureters), ureteroscopy in 11.3% (eight ureters) and open surgery in 8.5% (six ureters) of the renal units. The mean age of the patients was 10.67 +/- 4.4(1-16) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…In our work, following our diagnostic and therapeutic URS applications, have routinely applied a ureteral catheter in order to prevent renal colic as a result of small stone fragments and edema. This ureteral catheter is removed after 24 h. While the success rates of ureteral stone treatment by ureteroscopy vary between 86 and 94% in the relevant literature, this rate increases to 100% with secondary interventions [1][2][3][4][5][6][7][8][9][10][11][12]. Our success rate of 95.2% paralleled those reported in the literature.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In our work, following our diagnostic and therapeutic URS applications, have routinely applied a ureteral catheter in order to prevent renal colic as a result of small stone fragments and edema. This ureteral catheter is removed after 24 h. While the success rates of ureteral stone treatment by ureteroscopy vary between 86 and 94% in the relevant literature, this rate increases to 100% with secondary interventions [1][2][3][4][5][6][7][8][9][10][11][12]. Our success rate of 95.2% paralleled those reported in the literature.…”
Section: Discussionsupporting
confidence: 88%
“…In a study conducted by Borgmann et al in 1982, ureteral calculi were reported to constitute 7% of all stones occurring in children [9]. Today, the incidence of urinary system stone disease in children is known to increase continuously [3]. As a result of the complementary devices (electrohydraulic litothripsi (EHLT), pneumatic lithotriptor, basket catheters, forceps, etc.)…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Therefore, previous worries about the potential for injury to the ureteral mucosa, ureteral meatus, and urethra, especially in male youngsters, when using comparatively larger diameter instruments (11.5 Fr and 8.5 Fr), are no longer warranted. Instrument-related problems are now extremely rare due to the availability and effective usage of 4.5 Fr and 6.0 Fr semirigid ureteroscopes and 6.9 Fr flexible ureterorenoscope with a holmium:YAG laser energy source [ [34] , [35] , [36] , [37] ].…”
Section: Ureteroscopymentioning
confidence: 99%